2019
DOI: 10.1038/s41467-019-10311-z
|View full text |Cite
|
Sign up to set email alerts
|

Emergence of active nematics in chaining bacterial biofilms

Abstract: Growing tissue and bacterial colonies are active matter systems where cell divisions and cellular motion generate active stress. Although they operate in the non-equilibrium regime, these biological systems can form large-scale ordered structures. How mechanical instabilities drive the dynamics of active matter systems and form ordered structures are not well understood. Here, we use chaining Bacillus subtilis , also known as a biofilm, to study the relation between mechanical instabilit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
85
1
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(94 citation statements)
references
References 56 publications
5
85
1
3
Order By: Relevance
“…Additionally, topological defects, already well studied in the context of active nematics ( 24 , 51 , 62 66 ), play a role not only in the accumulation of particles ( 52 , 67 ) but also in shaping the dynamics. We find indeed that +1/2 topological defects act as “nematic wedges,” a particularly effective polarity-sorting mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, topological defects, already well studied in the context of active nematics ( 24 , 51 , 62 66 ), play a role not only in the accumulation of particles ( 52 , 67 ) but also in shaping the dynamics. We find indeed that +1/2 topological defects act as “nematic wedges,” a particularly effective polarity-sorting mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…Intriguingly, the functional role of topological defects has also been recently identified in a growing number of biological processes. Striking examples are cytoskeletal topological defects determining growth axis of animal Hydra [11,12], defects in cell orientation governing cell death and extrusion in epithelial tissues [13], defects in bacterial biofilms leading to layer formation [14], and defects as local hot spots of mound formation in neural stem cells [15].…”
mentioning
confidence: 99%
“…The constellation of topological defects and their dynamics within colonies of different bacterial morphologies have been described as two and three dimensional active nematic systems [51,[53][54][55]. Theoretically, the shape of growing bacterial colonies was explained using continuum approach wherein cells were treated as active gel growing in an isotropic liquid [53].…”
Section: Microbial Ecology: a Topological Perspectivementioning
confidence: 99%
“…Growth of bacterial monolayers under soft agarose surfaces demonstrated that topological defects were created at a constant rate, with the motility of +1/2 defects biased toward the colony periphery [54]. More recently, studies on bacterial monolayers were extended to analyze multilayer morphologies, capturing the early developmental stages of bacterial biofilms [51,55,56]. Analytical modeling and numerical simulations have revealed that the transition from mono to multilayered morphology (in bacterial colonies of rod-shaped cells) is triggered by a competition between the growth-induced in-plane active stresses and vertical restoring forces due to the cell-substrate interactions [51].…”
Section: Microbial Ecology: a Topological Perspectivementioning
confidence: 99%
See 1 more Smart Citation